Fertility and chromosome composition of wheat x jointed goatgrass backcross progeny - Beil, Craig T., author; Westra, Philip, advisor; Byrne, Patrick, advisor; Haley, Scott, committee member; Shaner, Dale, committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.
Keywords: gene escape; gene flow; genetically engineered; genomic in situ hybridization; interspecific hybridization; introgression